HUKUM ORGANISASI INTERNASIONAL SEBAGAI ALAT STABILITAS INTERNASIONAL - Hartana; Putu Artadi (Jurnal Pacta Sunt Servanda, 2021)
In the legal sense of international organizations, it is inseparable from the history of the establishment of international organizations themselves that have long appeared, namely when several countries enter into international relations and each of these countries has its own interests. International organizations, universal for maintaining world peace and security, have long been the thoughts of many statesmen, they want the international community to be organized. The research method used in this study is a normative legal research method, which is to collect material whose main source is legal material that contains normative rules. The use of primary data derived from international agreements and relevant laws and regulations in this study. This study examines the law of international organizations as a tool for international stability. The results of the study show that international law is used as sufficient protection for countries that are in conflict with other countries. The way of resolution in this international conflict is the peaceful handling of international conflicts through negotiations, discussion of issues with relevant parties to reach an agreement without the role of third parties, and this can be done bilaterally, multilaterally, formally or informally